Toxicology of antimicrobial nanoparticlesfor prosthetic devices - Nuñez-Anita RE (Dove Medical Press, 2014)
Rosa Elvira Nuñez-Anita,1 Laura Susana Acosta-Torres,2 Jorge Vilar-Pineda,2 Juan Carlos Martínez-Espinosa,3 Javier de la Fuente-Hernández, 2 Víctor Manuel Castaño4 1Facultad de Medicina Veterinariay Zootecnia, Universidad Michoacana de San Nicolás de Hidalgo, Tarìmbaro Municipio de Morelia, Michoacán, México; 2Escuela Nacionalde Estudios Superiores, Universidad Nacional Autónoma de México, Unidad León, Leòn Guanajuato, México; 3Unidad Profesional Interdisciplinaria de Ingenieria Campus Guanajuato, Instituto Politécnico Nacional, Leòn Guanajuato, México; 4Departamento de Materiales Moleculares, Centro de Física Aplicada y Tecnología Avanzada, Universidad Nacional Autónoma de México, Campus Juriquilla, Querètaro, México Abstract: Advances in nanotechnology are producing an accelerated proliferation of new nanomaterial composites that are likely to become an important source of engineered health-related products. Nanoparticles with antifungal effects are of great interest in the formulation of microbicidal materials. Fungi are found as innocuous commensals and colonize various habitats in and on humans, especially the skin and mucosa. As growth on surfaces is a natural part of the Candida spp. lifestyle, one can expect that Candida organisms colonize prosthetic devices, such as dentures. Macromolecular systems, due to their properties, allow efficient use of these materials in various fields, including the creation of reinforced nanoparticle polymers with antimicrobial activity. This review briefly summarizes the results of studies conducted during the past decade and especially in the last few years focused on the toxicity of different antimicrobial polymers and factors influencing their activities, as well as the main applications of antimicrobial polymers in dentistry. The present study addresses aspects that are often overlooked in nanotoxicology studies, such as careful time-dependent characterization of agglomeration and ion release. Keywords: cytotoxicity, oxidative stress, genotoxicity, antifungal effect, denture bases, dentistry